Answer:32
Step-by-step explanation:
768/24=32
Let's do this by Briot-Ruffini
First: Find the monomial root
x - 2 = 0
x = 2
Second: Allign this root with all the other coeficients from equation
Equation = -3x³ - 2x² - x - 2
Coeficients = -3, -2, -1, -2
2 | -3 -2 -1 -2
Copy the first coeficient
2 | -3 -2 -1 -2
-3
Multiply him by the root and sum with the next coeficient
2.(-3) = -6
-6 + (-2) = -8
2 | -3 -2 -1 -2
-3 -8
Do the same
2.(-8) = -16
-16 + (-1) = -17
2 | -3 -2 -1 -2
-3 -8 -17
The same,
2.(-17) = -34
-34 + (-2) = -36
2 | -3 -2 -1 -2
-3 -8 -17 -36
Now you just need to put the "x" after all these numbers with one exponent less, see
2 | -3x³ - 2x² - 1x - 2
-3x² - 8x - 17 -36
You may be asking what exponent -36 should be, and I say:
None or the monomial. He's like the rest of this division, so you can say:
(-3x³ - 2x² - x - 2)/(x - 2) = -3x² - 8x - 17 with rest -36 or you can say:
(-3x³ - 2x² - x - 2)/(x - 2) = -3x² - 8x - 17 - 36/(x - 2)
Just divide the rest by the monomial.
Answer:
∠ACB = 28.5
Step-by-step explanation:
In triangle ABC,
angle CAB = x-3
angle ABC = 4X-3
It is also given that AB=CB
We know that if two sides of any triangle are equal then corresponding sides must also be equal.
Hence
angle ACB = angle CAB
angle ACB = x-3 {Given that angle CAB = x-3 }
We know that sum of all three angles of a triangle is 180 degree so let's add given angles
angle ACB + angle CAB + angle ABC = 180
(x-3) + (x-3) + (4x-3) = 180
x-3 + x-3 + 4x-3 = 180
6x-9 = 180
6x = 180+9
6x = 189
x = 189/9
x= 31.5
Now plug value of x into
angle ACB = x-3 = 31.5-3 = 28.5
Hence final answer is
∠ACB = 28.5
Answer:
B) m∠ A'B'C' = m∠ABC
Step-by-step explanation:
A rotation does not change angle measure or side length. It preserves congruence.
This means that the image angle, A'B'C', will be congruent to the pre-image angle, ABC.